2013
DOI: 10.1177/1533317513488911
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Economic Burden of Newly Diagnosed Alzheimer’s Disease in a Medicare Advantage Population

Abstract: Members newly diagnosed with AD demonstrated greater HCRU, health care costs, and comorbidity burden compared to matched non-AD controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 36 publications
19
53
1
Order By: Relevance
“…A consistent finding of all studies comparing individuals with and without ADRD is that the average medical, nonmedical, and indirect costs of individuals with ADRD are higher than those of individuals without ADRD [6,7,12,15,1821], despite the differences in source of payment (Medicare, Medicaid, out-of-pocket), time period (lifetime vs. annual) and study population (e.g. decedents vs. all adults, AD vs. all forms of dementia), and stage of disease.…”
Section: Expert Commentarymentioning
confidence: 76%
See 1 more Smart Citation
“…A consistent finding of all studies comparing individuals with and without ADRD is that the average medical, nonmedical, and indirect costs of individuals with ADRD are higher than those of individuals without ADRD [6,7,12,15,1821], despite the differences in source of payment (Medicare, Medicaid, out-of-pocket), time period (lifetime vs. annual) and study population (e.g. decedents vs. all adults, AD vs. all forms of dementia), and stage of disease.…”
Section: Expert Commentarymentioning
confidence: 76%
“…Similar pattern was observed in another study using Medicare Advantage Prescription Drug plan dataset. This study revealed that during the year prior to diagnosis of ADRD, total medical expenditures were 44% higher, 1 year after diagnosis, the total medical expenditures were 2 times higher, and 2 years after diagnosis, the total medical expenditures were 1.7 times higher in the AD versus non-AD cohort [12]. In addition, the perceptions of physicians, patients, and family members regarding ADRD may also affect health-care utilization following an ADRD diagnosis.…”
Section: Economic Burden Of Adrd: Direct Medical Nonmedical and mentioning
confidence: 99%
“…These findings are similar to those from earlier studies that reported higher healthcare resource utilization and costs for individuals with Alzheimer's disease and dementia when compared with individuals without these conditions. [31][32][33][34] Individuals diagnosed with dementia are more likely to also be diagnosed with other comorbidities, 35 and to report greater difficulties in instrumental activities of daily living. 36 As a result, individuals with dementia may tend to use more LTC services and therefore incur higher LTC expenditure than non-dementia individuals.…”
Section: Discussionmentioning
confidence: 98%
“…AD affects approximately 5.4 million individuals in the United States and is estimated to affect up to 16 million by 2050 [33]. In Western countries, AD is the most prevalent form of dementia (45-60%), followed by vascular dementia (VD) (30-40%), and mixed dementia (10-20%), which in people older than 85 years of age may account for over 80% of the cases.…”
Section: Alzheimer's Diseasementioning
confidence: 99%